Rekonstruksi Onto-Epistemologi Filsafat Islam; Dialektika At-TurÄts dan Al-HadÄtsah Perspektif Al-Mestiry - Hijrian A Prihantoro (Religia, 2019)
The core of the paradigmatic disability of the world of Islamic thought, for Al-Mestiry, is the separation of the history of civilization from science. The challenge of modernity (tahaddiyât al-hadâtsah) of Muslims today is not only about the authentication (at-ta'shîl) of thought but at the same time about the revitalization of knowledge. The reading pattern of the structural dichotomy will never be able to accommodate knowledge in its entirety. For Al-Mestiry, the revolution of thought is an absolute requirement for generating civilization. Therefore, it is necessary to read integrally-dialectically through intra-epistema (at-tadâkhul al-ma'rifî) in the framework of total vision (ar-ru'yah al-kulliyyah) who heed the dialogical process of two points of view in it: ar-ru 'yah at-turâsiyyah and ar-ru'yah al-hadâtsiyyah. Thus, the momentum awareness (wa’yu al-mu'asharah) of change and renewal will teach humans about the openness of interpretation of the culture of religious thought (at-turâts).